IMPROVING ENGLISH LANGUAGE TEACHING AND PROFESSIONAL LANGUAGE ACTIVITIES IN TECHNICAL COLLEGES OF UZBEKISTAN: EDUCATIONAL REFORMS AND PEDAGOGICAL OUTCOMES - Karimova Mavludaxon (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The ongoing modernization of the education system in Uzbekistan has significantly influenced foreign language education, particularly in vocational and technical institutions. English language proficiency has become a strategic priority due to increasing international cooperation, labor mobility, and technological development. This study analyzes the implementation of recent educational reforms in English language teaching (ELT) within technical colleges and examines how language instruction is integrated with professional training activities. The research applies qualitative policy analysis and pedagogical evaluation methods to examine curriculum transformation, teacher professional development, and communicative teaching practices. The findings indicate that competency-based instruction, professionally oriented language activities, and digital learning environments contribute to improved communicative competence and student motivation. However, institutional disparities and methodological challenges remain. The study concludes that sustainable improvement in English language education requires continuous professional development, industry collaboration, and alignment with international educational standards.